PERUBAHAN POLA RUANG RUMAH TINGGAL TRADISIONAL MELAYU PONTIANAK DI SEKITAR KOMPLEK KRATON KADRIYAH PONTIANAK KALIMANTAN BARAT - , Wahyudin Ciptadi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Malay traditional housing in Pontianak is a single-family dwelling which is the smallest social unit. It is generally influenced by the teachings of Islam, the customs of the Malay Pontianak, and the Kadriyah Palace of Pontianak that still stands to this day. In relation to the classification of the types of the Malay traditional housing in Pontianak based on the highest hierarchical level, it can be classified into the Limas Style type (Potong Limas), the Godang Style type (Potong Godang), and the Kawat Style type (Potong Kawat). The phenomenon that occurs among the Malay people of Pontianak living around the Kadriyah Palace of Pontianak nowadays is that there are some people who still adhere to customs and traditions of the Malay people of Pontianak as well as the customs and traditions derived from the Kadriyah Palace of Pontianak. However, on the other hand, there are also some people that belong to a sub group of the Malay people of Pontianak who have already followed the paradigm development and shift of thinking (changing ways of thinking). This development affects the culture of this sub group of the Malay people of Pontianak related to the activities, the physical appearance, the spatial pattern of the current housing. Therefore, there are parts that are still maintained and there are also parts that have changed. This research provides an overview related to changes in the spatial pattern of the Malay traditional housing in Pontianak and determines any factors that may affect the occurrence of changes in the spatial pattern of the Malay traditional housing in Pontianak around the area of the Kadriyah Palace. This research employed a method of a qualitative rationalistic approach. This research employed several stages of the implementation process, namely: the data collection stage (initial observations, further observations, and interviews) and the stages of the data analysis and the discussion of the research findings. To analyze changes in the spatial pattern that occur, the initial floor plan and the current floor plan that are functional in nature of those all three types of the Malay traditional housing in Pontianak were used.This research concludes that there are changes in the spatial pattern of those all three types of the Malay traditional housing in Pontianak that include a variety of aspects, namely: the spatial organization, the spatial hierarchy, the spatial orientation, and the spatial relations. In addition, the factors that can influence changes in the spatial pattern of the Malay traditional housing in Pontianak are internal factors (including: increased number of family members, changes and development of needs, as well as changes and development of lifestyle and the value system) and external factors (including: social, cultural, economic, religious, technological and geographical aspects).